FEATURES AND METHODOLOGY OF THE INDUSTRIAL AND TOURIST ZONING (ON THE EXAMPLE OF KRYVYI RIH REGION) - Пацюк, Вікторія (Human Geography Journal, 2015)
Main point of the concept of "industrial and tourist zoning" has been presented in the article; the criteria of selection of different taxonomical units have been pointed out as well as principles of their organization;methodology of the individual and typological industrial and tourist zoning of industrial region has been approved by the example of Kryvyi Rih region. Tourist rating of industrial-touristic subzones of Kryvyi Rih region as well as level of tourist potential have been defined on the ground of criteria of industrial and touristic units.